2023
DOI: 10.5114/biolsport.2023.116452
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet improves metabolic flexibility during progressive exercise to exhaustion (VO 2 max testing) and during 5km running time trials

Abstract: Recently we reported similar performances in both progressive tests to exhaustion (VO 2 max) and 5km running time trials (5KTT) after consuming low-carbohydrate, high-fat (LCHF) or high-carbohydrate, low-fat (HCLF) diets. Accordingly, we tested the null hypothesis that the metabolic responses during both tests would be similar across diets. In a randomized, counterbalanced, cross-over design, seven male athletes (VO 2 max: 61.9 ± 6.1 mL/kg/min; age: 35.6 ± 8.4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 46 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…First, amongst the highest rates of fat oxidation (1.5 g/min) yet measured were recorded in the Olympic-class racewalkers following adoption of a LCHF diet for just 5 days ( Burke et al, 2017 ; Burke et al, 2021 ). These data are very similar to those measured in recreational but well-trained runners who had adapted to the LCHF diet for 6 weeks ( Prins et al, 2019 ; Prins et al, 2023b ). While these rapid adaptations may be partially explained by elite-level fitness ( Rothschild et al, 2022 ), recent analyses have demonstrated that respiratory quotient and substrate oxidation changes occur in 4 days in male endurance athletes on an isocaloric LCHF diet ( Prins et al, 2019 ), within 7 days ( Hall et al, 2016 ) and 14 days in moderately trained athletes ( Cipryan et al, 2018 ) and overweight/obese subjects ( Buga et al, 2021 ; Hall et al, 2021 ), as biochemical changes consistent with increase fat oxidation (i.e., reduced glucose and insulin load; increase ketones) occur upon the first 24 h following reduced carbohydrate intake (<50 g/day) ( Hengist et al, 2022 ).…”
Section: Low-carbohydrate High-fat Diets and The Crossover Pointsupporting
confidence: 82%
See 3 more Smart Citations
“…First, amongst the highest rates of fat oxidation (1.5 g/min) yet measured were recorded in the Olympic-class racewalkers following adoption of a LCHF diet for just 5 days ( Burke et al, 2017 ; Burke et al, 2021 ). These data are very similar to those measured in recreational but well-trained runners who had adapted to the LCHF diet for 6 weeks ( Prins et al, 2019 ; Prins et al, 2023b ). While these rapid adaptations may be partially explained by elite-level fitness ( Rothschild et al, 2022 ), recent analyses have demonstrated that respiratory quotient and substrate oxidation changes occur in 4 days in male endurance athletes on an isocaloric LCHF diet ( Prins et al, 2019 ), within 7 days ( Hall et al, 2016 ) and 14 days in moderately trained athletes ( Cipryan et al, 2018 ) and overweight/obese subjects ( Buga et al, 2021 ; Hall et al, 2021 ), as biochemical changes consistent with increase fat oxidation (i.e., reduced glucose and insulin load; increase ketones) occur upon the first 24 h following reduced carbohydrate intake (<50 g/day) ( Hengist et al, 2022 ).…”
Section: Low-carbohydrate High-fat Diets and The Crossover Pointsupporting
confidence: 82%
“…Since Prins et al (2019) performed VO 2 max tests in their subjects when eating either the LCHF or HCLF diets for 6 weeks, they were able to study the effects of this dietary change on the crossover point during progressive exercise to exhaustion [( Prins et al, 2023b ); Figure 3 ]. Interestingly, Figure 3 (left panel) shows that when eating the HCLF diet subjects did not show a definitive crossover point.…”
Section: Low-carbohydrate High-fat Diets and The Crossover Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…Countering this evidence is a growing body of data demonstrating that extended habituation to a low-carbohydrate high-fat (LCHF) diet can shift the "cross-over" set-point in favor of greater fat oxidation, even at much higher intensities [(< 85% VO 2max ); (27,28)], and dramatically increase the rates of peak fat oxidation at moderate intensities (i.e., 60% VO 2max ) (29). Rates of fat oxidation during exercise across these LCHF studies are amongst the highest yet measured (24,25,28,(30)(31)(32) even though they were measured during progressive exercise to exhaustion (e.g., minutes), rather than more prolonged exercise (e.g., hours). These studies opened key questions of whether performance-equivalence would still hold (i) if exercise intensity was increased (i.e., running trial 800-1,609 m) and (ii) if high-intensity interval sessions would facilitate more muscle glycogen depletion in those habituated to LCHF which would become more apparent as the number of intervals increased.…”
Section: Introductionmentioning
confidence: 99%